(untitled) (Intercom - Brazilian Journal of Communication Sciences, 2023)
This article presents the analysis of scientific publications on the themes of gender and communication from the beginning of the fourth feminist wave (2013) until 2019. Therefore, this text is divided into two methodological phases. In the first one, inspired by Systematic Review Protocols, we collected data in the SciELO database and found 71 texts from different areas. We refined the results and selected 15 articles for the second phase, the qualitative Content Analysis. The results obtained in the classification demonstrate that, although the texts deal with gender issues and mention several fourth-wave themes – such as harassment, gender violence, and intersectionality –, only four have a feminist approach. The corpus references show that the authors with more representativeness and citations are Joan Scott and Judith Butler, and they make it possible to affirm that there are little interactions within some areas (Sports, Communication, and Health). Nevertheless, they show the lack of dialogue that prevails in the set of research on these themes in Portuguese